Novel Antiparasitic Activity of the Antifungal Lead Occidiofungin - Ma, Jingbo (Antimicrob Agents Chemother, 2020)
Novel antiparasitic activity was observed for the antifungal occidiofungin. It efficaciously and irreversibly inhibited the zoonotic enteric parasite Cryptosporidium parvum in vitro with limited cytotoxicity (50% effective concentration [EC(50)] = 120 nM versus 50% cytotoxic concentration [TC(50)] = 988 nM), and its application disrupted the parasite morphology. This study expands the spectrum of activity of a glycolipopeptide named occidiofungin. Occidiofungin has poor gastrointestinal tract absorption properties, supporting future investigations into its potential activities on other enteric parasites.